THE 10s SOLUTION IN DEALING WITH GRADE INFLATION IN HIGHER EDUCATION: DOES IT MAKE SENSE? - Tengku Nazatul Shima Tengku Paris; Mohammad Nasrul Hakim Roslan; Hapini Awang; Norma Aisyah Malkan; Maziah Mahmud; Ramlan Mustapha (Journal of Islamic, Social, Economics and Development, 2023)
Globally, grades or marks are used as a fundamental sorting and signaling method for students at all levels of education, from primary schools to universities. Grades given to pupils should be reflective of their progress in learning. Over the past three decades, grade inflation has been endemic in the American educational system, drawing considerable criticism from teachers, scholars, and the general public. Thus, this study aims to examine the Nominal Group Technique (NGT) as a potential alternative approach for addressing the issue of grade inflation. Researchers have employed this methodology to offer resolutions to the issue of grade inflation in higher education. The summary of expert recommendations has identified a total of ten options for addressing grade inflation. Furthermore, the study's results indicate that the NGT technique has proven to be an effective means for swiftly and effortlessly attaining element validation. This success may be attributed to the meticulous development of elements through a comprehensive review of existing literature, followed by rigorous discussions and voting to establish expert consensus. Recommendations for future research are proposed in order to enhance the quality of the study, with a particular focus on collaborating with experts to develop precise guidelines for addressing these issues.